An investigation on discharge fault in buffer layer of 220 kV XLPE AC cable - Boxue Du; Xiaoyu Du; Xiaoxiao Kong; Jin Li; Zhijian Li; Xu Li (IET Science, Measurement & Technology, 2021)
Abstract Discharge failure mechanism of the cable buffer layer is investigated in this paper by the analysis of causes and characteristics of partial discharge (PD) behaviours in the case of failure. The obtained results show that both the volume resistivity and the surface resistance of the buffer layer increase as the relative humidity is elevated. It is found that the electric field distribution inside the buffer layer is distorted when there is poor contact condition and aggravated with the increase of the volume resistivity by the finite element analysis. PD behaviours analysis shows that the PD intensity is closely related to the contact state of the buffer layer, and hence the latter can be reflected by statistical parameters like the maximum pulse amplitude and the average equivalent frequency. The conclusions indicate that the electric field distortion is caused by the variation of the contact state of the buffer layer and the deterioration, which is responsible for the occurrence of PD. Therefore, the PD detection for the suspected faulty cables provides an effective method for the state evaluation of the buffer layer.